Mounties, Moose, and Moonshine: The Patterns and Context of Outport Crime - Okihiro, Norman (Heritage, 1997)
Okihiro looks at crime arising from economic subsistence behaviours ? hunting, gathering, and domestic production activities long supported or tolerated in the outports, including big-game poaching and the production and consumption of moonshine.